Fostering Nationalism Among Students of Sanggar Bimbingan Sungai Buloh in Malaysia - Nabila Salma Hasnai; Nuran Farah Dhianuary; Nuriya Hazma Arifatul Ulya; Dwi Puji Lestarianingrum; Hery Siswanto (Asosiasi Lembaga Pendidikan Tenaga Kependidikan Peguruan Tinggi Muhammadiyah dan Aisyiyah, 2023)
This research is aimed at understanding the efforts to instill nationalism among the students of Sanggar Bimbingan Sungai Buloh, Malaysia. The study employs a qualitative method, and for data collection, observation is used by observing the students' activities of singing National and Regional songs as a form of instilling nationalism among the students of Sanggar Bimbingan. The results indicate that the introduction and implementation of National songs can assist in instilling a sense of nationalism among the students of Sanggar Bimbingan Sungai Buloh